Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jor.24112
|View full text |Cite
|
Sign up to set email alerts
|

Initial cell plating density affects properties of human primary synovial mesenchymal stem cells

Abstract: Synovial mesenchymal stem cells (MSCs) appear to be an attractive cell source in cartilage and meniscus regeneration because of their high proliferative and chondrogenic potentials. Two methods are used to culture synovial nucleated cells in the preparation of primary synovial MSCs. In one method, the cells are plated at low density to make cell colonies. In the other method, the cells are plated at high density. We investigated the effects of initial cell density on proliferation, surface markers, and multipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In our recent report, we plated the synovial nucleated cells at 10 3 , 10 4 , or 10 5 cells/60 cm 2 dish and cultured them for 14 days. The fold increase was negatively related to plating density, whereas the total number of cells/dish was positively related to plating density [5]. In our current study, we did similar experiments at densities of every 300 cells/60 cm 2 dish rather than every 10 times that many cells/60 cm 2 dish, and similar results were obtained.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our recent report, we plated the synovial nucleated cells at 10 3 , 10 4 , or 10 5 cells/60 cm 2 dish and cultured them for 14 days. The fold increase was negatively related to plating density, whereas the total number of cells/dish was positively related to plating density [5]. In our current study, we did similar experiments at densities of every 300 cells/60 cm 2 dish rather than every 10 times that many cells/60 cm 2 dish, and similar results were obtained.…”
Section: Discussionsupporting
confidence: 82%
“…Third, this study did not consider chondrocyte differentiation potential. In our recent report, the cartilage pellet weight was negatively related to the initial plating density [5].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the MSCs do not show uniform colony-forming abilities 57 due to differences in their differentiation ability 8 . Interestingly, even when MSCs in the same population are cultured, the initial cell density affects the colony size, resulting in differences in cartilage differentiation ability 9 . Colony information could therefore predict the characteristics of the MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the influence of culture conditions on stem cell potential, Nakamura et al examined the effects of initial cell plating density on the growth and multipotency of synovial stem cells and found that the initial significantly affects stem cell proliferation and chondrogenic potential.…”
mentioning
confidence: 99%